Measurement of the airflow velocity upstream and downstream a wire mesh using constant temperature anemometry - Lízal, František; Tuhovčák, Ján; Jícha, Miroslav (EDP Sciences, 2013)
Measurement of velocity upstream and downstream a special wire mesh was performed to ascertain the effect of the mesh on the flow. The mesh consisted of two components, a basic rectangular mesh with mesh width 1.22 mm and wire diameter 0.2 mm, and a top steel wool with random position of wires and wire diameter 0.05 mm. The velocity was measured by Constant Temperature Anemometry using single wire probe in a Plexiglas channel of rectangular cross-section. As a first step, measurement of one horizontal and one vertical measuring line was performed 10 mm upstream and 6 mm downstream the wire mesh. A spatial velocity profile upstream of the wire mesh was smooth, while the downstream velocity profile was highly disturbed. However, velocity fluctuations expressed in terms of turbulence intensity downstream of the wire mesh were attenuated down to 1%. Further measurements of the area downstream the wire mesh will be performed to describe the development of the flow.

Measurement of velocity upstream and downstream a special wire mesh was performed to ascertain the effect of the mesh on the flow. The mesh consisted of two components, a basic rectangular mesh with mesh width 1.22 mm and wire diameter 0.2 mm, and a top steel wool with random position of wires and wire diameter 0.05 mm. The velocity was measured by Constant Temperature Anemometry using single wire probe in a Plexiglas channel of rectangular cross-section. As a first step, measurement of one horizontal and one vertical measuring line was performed 10 mm upstream and 6 mm downstream the wire mesh. A spatial velocity profile upstream of the wire mesh was smooth, while the downstream velocity profile was highly disturbed. However, velocity fluctuations expressed in terms of turbulence intensity downstream of the wire mesh were attenuated down to 1%. Further measurements of the area downstream the wire mesh will be performed to describe the development of the flow.
Measurement of the airflow velocity upstream and downstream a wire mesh using constant temperature anemometry
Keywords: constant temperature anemometry; velocity; wire mesh; wire screen; constant temperature anemometry; velocity; wire mesh; wire screen